Studi Keanekaragaman Jenis Burung Di Kawasan Ekoeduwisata Daerah Aliran Sungai (DAS) Ciliwung - Asep Koswara; Tatang Mitra Setia; Dewi Malia Prawiradilaga (Jurnal Pro-Life, 2022)
The limited study of bird in The Ecoturism area of Ciliwung watershed has led to the inability of the management authority to inform the community about diversity of birds in this area. The purpose of this study is to find out the composition, abundance, and diversity of bird species. The research was carried out in March – July 2021 at 14 observation points divided into 2 research stations called: Saung Matpeci and Shibi. Saung Matpeci Station has five observation points, and Shibi Station has nine observation points. The method used was Point Count method. and the bird diversity was analysid using the Shannon-Wiener Index. There were 518 individuals consisting of 38 species, 26 genera and 19 families of birds. The highest bird abundance value in this area was 0,247 and the lowest abundance was 0,002. The diversity of bird in this area was classified into moderate category (2,54). The Brontok eagle (Nisaetus cirrhatus) and The Striped fan (Rhipidura javanica) are protected birds in Indonesia